The Use of Supplementary Materials for Teaching Children in EFL Classes - Galán Chérrez, Nefi Manuel (2012)
This research project is about the use of supplementary materials for teaching children in EFL classes. The purpose of this study is to find out whether educators in Ecuador are using supplementary materials for the teaching of English as a foreign language or if they are not using them at all. In addition, the use of supplementary materials enhances children’s performance because they learn through interaction with these tools. The investigation took place in the city of Loja at a private institution where English is taught to people from all ages and levels. The general approach of this study is Qualitative and Quantitative. The aspects taken into account for the qualitative analysis were: pertinence, appropriateness, and quality of each supplementary material in every observed class. Furthermore, the aspects that were taken into consideration for the quantitative analysis were: frequency of use of each supporting material; personal criteria based on observation, surveys and interviews. Subsequently, the instruments employed in this investigation were data collection formats, observation formats, tables and questionnaires. According to the results, the most used material is the whiteboard.